O espaço que a obra Frankenstein (1831) ocupa no filme biográfico Mary Shelley (2017): um ato socialmente simbólico - Santos, Sandra Mendonça Soares dos (2025)
This dissertation aims to investigate the transcreation of the film Mary Shelley, directed by Haifaa al Mansour and written by Emma Jensen, by considering biographical and literary aspects to examine the space that Mary Shelley's poetics occupies in the cinematic narrative. In the biopic, the filmmaker transcreates the life of the author, suggesting that elements of her experience as a woman in a nineteenth century patriarchal society are represented in the main characters of her novel. Thus, moments from Mary Shelley's life are intertwined with the narrative of Frankenstein. Based on the concept of transcreation proposed by Haroldo de Campos and the sociological criticism developed by Fredric Jameson, this study analyzes how the filmmaker engages with the novel and, through transcreation, what she chooses to omit—since every formal choice is revealing. The filmic reading is, to some extent, semantically expanded, as Jameson (1992) suggests, going beyond the manifested content to reach a more advanced horizon of interpretation that aligns with a feminist critique of the novel. However, other aspects remain unexplored, perhaps due to limitations imposed by the filmmaker’s background or the socio-historical context of her time. Therefore, a deeper analysis of Mary Shelley's life and work will be carried out in order to understand why the filmmaker does not advance to a third horizon of interpretation, and how the consciousness developed by the novelist in the nineteenth century has traveled through time and space to reach a filmmaker who, in many ways, faces the same challenges in the twenty-first century.